2021
DOI: 10.3390/cells10071828
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphatidylserine Receptor TIM-1 Enhances Authentic Chikungunya Virus Cell Entry

Abstract: Chikungunya virus (CHIKV) is a re-emerging, mosquito-transmitted, enveloped positive stranded RNA virus. Chikungunya fever is characterized by acute and chronic debilitating arthritis. Although multiple host factors have been shown to enhance CHIKV infection, the molecular mechanisms of cell entry and entry factors remain poorly understood. The phosphatidylserine-dependent receptors, T-cell immunoglobulin and mucin domain 1 (TIM-1) and Axl receptor tyrosine kinase (Axl), are transmembrane proteins that can ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 107 publications
(168 reference statements)
2
36
0
Order By: Relevance
“…Interestingly, viruses seem to preferentially use one PS receptor over others. TIM-1 is preferentially used by EBOV, CHIKV, and DENV, whereas SARS-CoV-2 or ZIKV entry is preferentially enhanced by AXL [ 7 , 25 , 39 , 40 ]. The mechanism driving this distinction is unknown.…”
Section: Enveloped Virus Utilization Of Ps Receptors: Tools Of the Tradementioning
confidence: 99%
“…Interestingly, viruses seem to preferentially use one PS receptor over others. TIM-1 is preferentially used by EBOV, CHIKV, and DENV, whereas SARS-CoV-2 or ZIKV entry is preferentially enhanced by AXL [ 7 , 25 , 39 , 40 ]. The mechanism driving this distinction is unknown.…”
Section: Enveloped Virus Utilization Of Ps Receptors: Tools Of the Tradementioning
confidence: 99%
“…Additionally, other phosphatidylserine binding proteins, such as Axl and TIM-4, have also been demonstrated to facilitate CHIKV infection [ 51 ]. However, a recent independent study showed that only TIM-1, unlike Axl, is functional as an entry factor for CHIKV infection [ 52 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…Numerous enveloped viruses including dengue virus [11,12], Ebola virus (EBOV) [11,[13][14][15][16][17][18], chikungunya virus [11,13,19], vaccinia virus [20][21][22], and others [11,13,19,[23][24][25][26][27][28][29][30][31][32][33] utilize PtdSer receptors for initial host cell attachment, a mechanism termed apoptotic mimicry (Fig 2A). PtdSer within the outer leaflet of the viral envelope mediates binding to PtdSer receptors on phagocytic cells that typically recognize PtdSer-coated apoptotic bodies.…”
Section: Entry Through Apoptotic Mimicrymentioning
confidence: 99%